THE EFFECTIVENESS OF USING ENGLISH SONGS TO IMPROVE VOCABULARY MASTERY AMONG EFL ELEMENTARY SCHOOL STUDENTS IN SETU BABAKAN AREA - Elsa Fadhila (ELLTER Journal, 2022)
Vocabulary refers to words that people use to communicate with others. Vocabulary plays as a fundamental role in learning a language and make English vocabulary mastery as the most important skill that a person needs to master before having the other English skills. This study aims to analyze the effectiveness of English songs to teach English vocabulary for elementary school students. This study applied quantitative research with one group pretest-posttest pre-experimental research design to analyze whether the media chosen in this study is effective to be used in English vocabulary learning classes. A total of 20 elementary school students who learnt in Fun Course program chosen as the samples using purposive sampling. Paired sample t test was analyzed and obtained tcount 8,156 at α = 0,05 (5%) ttable 1,729 (tcount 8,156 > ttable 1,729). Thus, the alternative hypothesis (Ha) in this study is accepted and null hypothesis (H0) in this study is rejected which states that there is a significant effectiveness of using English songs in improving elementary school students’ vocabulary mastery in RT 9, Setu Babakan area.